A new species of the genus Criotettix Bolivar (Orthoptera:Tetrigoidea:Scelimenidae) from Zhejiang, China - Zhang, Yu-Long; Li, Xin-Jiang; Zhi, Yong-Chao (Zootaxa, 2019)
A new species of the genus is described from Zhejiang, China in this paper. The new species Criotettix zhejiangensis sp. nov. is similar to Criotettix strivertexoides Zheng, Wei & Li, 2009, but differs in antennae placed the lower margin of eye, head exserted above the pronotal surface, lateral keels in prozona slightly contracted backward, upper margin of pronotum not waved in lateral view, width of tegmen 1.2 times width of mid leg femur and lower side of hind femur not black. The new species is also similar to Criotettix strivertex Zheng, Wei & Li, 2009, it differs from latter by head exserted above the pronotal surface, upper margin of pronotum not waved in lateral view, lower side of mid femur straight, width of tegmen 1.2 times width of mid leg femur and length of hind femur 3.1 times its width. The type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, China.